Critical Thinking Tasks in ESP Speaking Classes: A Qualitative Exploration of 21st Century Skills Development - Awalia Azis; Ika Satrawati; Anwar Taufiq; Yuriatson Jubhari; Dzur Rif'ah Mahmudah (CV. Eureka Murakabi Abadi, 2025)
Humans expect English for Specific Purposes (ESP) classes in the 21st century to not only help students get better at speaking and writing English, but also to help them think critically and communicate professionally. The goal of this study was to find out how critical thinking tasks are used in an ESP speaking class and how they help second-semester students in the Primary School Teacher Education (PGSD) program at Muhammadiyah University of Makassar build abilities they would need in the 21st century. A qualitative descriptive design was used to collect data from nine students using semi-structured interviews and observations of the classroom. Thematic analysis showed that critical thinking exercises helped students solve problems in the real world, explain and defend their ideas, and work well with others in group conversations. Even though participants had trouble with terminology and expression, they said they felt more confident, more conscious of their thinking, and more ready for work. The study concludes that critical thinking exercises in ESP speaking classes help students learn the language and develop skills that are important in the 21st century. It also suggests that authentic assignments with enough assistance should be used to help students succeed.